2016
DOI: 10.33225/jbse/16.15.760
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distance and Pro-Environmental Behavior: An Application of Behavior Model to Emerging Contaminants in Higher Education

Abstract: To help mitigate and educate the negative impacts of emerging contaminants (ECs), this research tried to realize the environmental attitude and environmental behavioral intention of students in the field of environmental education at higher education level. However, little is known about integration of psychological distance, environmental attitude, behavioral intention and effective teaching strategies on emerging contaminants for undergraduate students within a behavior model. This research proposed a pro-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 83 publications
(97 reference statements)
2
5
0
2
Order By: Relevance
“…Acorde con esto, Mtutu & Thondhlana (2016) encontraron que para desencadenar un comportamiento ambiental no basta con poseer una conciencia ambiental, se precisa de factores situacionales como contenedores de reciclaje adecuados que, combinado con el deseo de mantener buenas relaciones sociales, alientan un comportamiento ambiental (Fang et al, 2016). Aunque también, se ha planteado que ciertas acciones en beneficio del medio ambiente pueden darse por preocupaciones no ambientales como el deseo de ahorrar dinero, tener mayor tiempo para la vida social o por sentido de competencia personal, por ejemplo (Stern, 2000).…”
Section: Comportamiento Ambientalunclassified
See 1 more Smart Citation
“…Acorde con esto, Mtutu & Thondhlana (2016) encontraron que para desencadenar un comportamiento ambiental no basta con poseer una conciencia ambiental, se precisa de factores situacionales como contenedores de reciclaje adecuados que, combinado con el deseo de mantener buenas relaciones sociales, alientan un comportamiento ambiental (Fang et al, 2016). Aunque también, se ha planteado que ciertas acciones en beneficio del medio ambiente pueden darse por preocupaciones no ambientales como el deseo de ahorrar dinero, tener mayor tiempo para la vida social o por sentido de competencia personal, por ejemplo (Stern, 2000).…”
Section: Comportamiento Ambientalunclassified
“…Ligado a lo expuesto, según lo planteado por Fang et al (2016), las teorías y modelos buscan identificar y comunicar los riesgos e incertidumbres subyacentes a las decisiones de intención de comportamiento ambiental de los individuos; se persigue la comprensión del comportamiento ambiental a través de variables causales influidas por factores como la actitud, las fuerzas contextuales, las capacidades personales y los hábitos y rutinas de cada persona (Stern, 2000). En este sentido, una de las teorías que ha sido de gran aceptación para el estudio del comportamiento ambiental es la Teoría del Comportamiento Planificado (TCP) propuesta por Icek Ajzen la cual se aborda en el siguiente apartado.…”
Section: Comportamiento Ambientalunclassified
“…Several studies found that increased PD was related to lower willingness to engage in mitigating Carmi & Kimhi, 2015;Spence et al, 2012;Verplanken et al, 2020;Wang et al, 2019, Study 1;Xu et al, 2020) or adaptive behaviours (Azadi et al, 2019;. Others found no direct relationship (Chen, 2019;Wang et al, 2019, Study 2) or a full or partial mediation by concern (Chen, 2020;Spence et al, 2012), environmental attachment and conservation commitment (Fang et al, 2016), environmental ethics and perceived responsibility (Yu et al, 2017) or perceived self-capacity and vulnerability (Rodríguez-Cruz & Niles, 2021). Similarly, regarding policy support, some studies found that other variables were more important predictors than PD Wang et al, 2019), or suggest a mediation by concern (Singh et al, 2017).…”
Section: Associations Of Psychological Distance With Other Conceptsmentioning
confidence: 99%
“…Feeling uncertain about climate change will therefore be captured as both high scepticism and large hypothetical distance. Further, pro-environmental attitudes towards nature and environmental protection , conservation commitment and environmental attachment (Fang et al, 2016), environmental ethics (Yu et al, 2017), the new ecological paradigm (Chen, 2020;Verplanken et al, 2020), the belief in a fragile environment (Wang et al, 2019) and a green self-identity (Verplanken et al, 2020), were all related to decreased PD. These relationships with stable characteristics support a conceptualisation of PD of climate change as relatively stable too.…”
Section: Associations Of Psychological Distance With Other Conceptsmentioning
confidence: 99%
“…Empirical studies support that meaning in life is positively associated with prosocial behavior (Chang & Xie, 2018; Fang & Chang, 2019; Wang et al, 2018). For instance, Chinese college students have demonstrated a positive link between meaning in life and prosocial behavior (Chang & Xie, 2018; Fang & Chang, 2019). The established links between RESE and meaning in life and between meaning in life and prosocial behavior imply that meaning in life may be the path to RESE and prosocial behavior; thus, we hypothesized that meaning in life mediates the linkage between RESE and prosocial behavior.…”
Section: Introductionmentioning
confidence: 99%